H2 and CO erosion resistant Al2O3-Cr2O3 refractory material for hydrogen-based shaft furnace and preparation method of H2 and CO erosion resistant Al2O3-Cr2O3 refractory material
By using aluminum oxide-chromium oxide refractory materials made of raw materials such as chromium corundum, aluminum-chromium slag, etc., the (Cr, Al, Er) 2O3 composite solid solution is formed, which solves the problem that existing refractory materials cannot resist hydrogen and carbon monoxide corrosion, and significantly improves the service life and thermal shock resistance of the hydrogen-based vertical furnace.
Patent Information
- Application Number
- CN202411844100.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-15
- Publication Date
- 2025-03-21
AI Technical Summary
Existing refractory materials cannot effectively resist the erosion of hydrogen and carbon monoxide, resulting in a short service life of hydrogen-based vertical furnaces.
Alumina-chromium oxide refractory material made of chromium corundum, aluminum chromium slag, electromelted white corundum powder, aluminum oxide fine powder, chromium oxide green and erbium oxide are used to form (Cr, Al, Er) 2O3 composite solid solution through pre-firing and sintering process to enhance corrosion resistance.
The refractory material exhibits significant resistance to H2 and CO gas erosion under high temperature environments, improves the service life of the hydrogen-based vertical furnace, and has good thermal shock resistance and economic benefits.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of refractory materials, and in particular to an Al2O3-Cr2O3 refractory material resistant to H2 and CO corrosion for a hydrogen-based vertical furnace and a preparation method thereof. Background Art
[0002] Traditional blast furnace ironmaking uses coke combustion to provide the heat required for the reduction reaction and produce the reducing agent CO, which reduces iron ore to iron and produces a large amount of CO2. Hydrogen metallurgy uses hydrogen instead of CO as a reducing agent, and its reduction product is water. The hydrogen-based vertical furnace direct reduction process uses hydrogen-rich or full hydrogen reducing gas as a reducing agent, with low process energy consumption and strong carbon reduction capacity. However, the requirements for furnace lining refractory materials are also relatively higher.
[0003] CN114315323A records an Al2O3-Cr2O3 refractory product with chrome corundum as aggregate. The Al2O3-Cr2O3 refractory product with chrome corundum as aggregate includes aggregate and matrix; the aggregate is fused Al2O3-Cr2O3 particles, and the aggregate content is 55% to 75% of the total mass of the raw material; the matrix contains Al2O3-Cr2O3 fine powder or one or a combination of components that can form Al2O3-Cr2O3 solid solution, and a thermal shock resistant agent or a sintering aid is added to the matrix; the matrix content is 25% to 45% of the total mass of the raw material; the aggregate and the matrix are mixed evenly with a binder, and then pressed into a machine shape, and then dried and sintered into a product. This refractory product resists the preferential erosion and disintegration of the material particles by alkali metal oxides, halogen salts, etc., but cannot resist the erosion of H2 and CO gases.
[0004] Therefore, in order to extend the service life of the hydrogen-based vertical furnace, it is necessary to develop an Al2O3-Cr2O3 refractory material resistant to H2 and CO corrosion for the hydrogen-based vertical furnace and a preparation method thereof. Summary of the invention
[0005] In order to solve the deficiencies in the prior art, the present invention provides an alumina-chromium oxide refractory material resistant to H2 and CO corrosion for a hydrogen-based vertical furnace and a preparation method thereof. The present invention has better performance, high melting point, high hardness, high strength, good corrosion resistance and thermal shock resistance, and a dense structure, high bulk density, low porosity, easy construction and use, and a long service life.
[0006] In order to achieve the above object, the specific scheme adopted by the present invention is: A H2 and CO erosion resistant Al2O3-Cr2O3 refractory material for a hydrogen-based vertical furnace, comprising the following raw materials in parts by weight: 30-40 parts of chrome corundum particles with a particle size of 4-1mm; 10-15 parts of aluminum chrome slag particles with a particle size of 1-0mm; 10-20 parts of fused brown corundum particles with a particle size of 3-1mm; 20-30 parts of fused white corundum powder with a particle size less than 0.074mm; 5-10 parts of alumina powder with a particle size less than 6μm; 3-5 parts of chromium oxide green with a particle size less than 0.074mm; 3-4 parts of phosphoric acid; 3-10 parts of erbium oxide.
[0007] The weight percentage of Cr2O3 in the chrome corundum particles is ≥96%; The aluminum-chrome slag is obtained by crushing waste aluminum-chrome bricks, and the weight proportion of Cr2O3 in the aluminum-chrome slag particles is ≥36%; The weight percentage of Al2O3 in the fused white corundum powder is ≥99.5%; The weight percentage of Al2O3 in the fused brown corundum particles is ≥95%; The weight percentage of Al2O3 in the alumina powder is ≥99.5%; Among them, H3PO4 in phosphoric acid ≥ 85%; The particle size of erbium oxide is 5um.
[0008] A method for preparing an Al2O3-Cr2O3 refractory material resistant to H2 and CO corrosion for a hydrogen-based vertical furnace mainly comprises the following steps: Step 1, weighing each raw material according to the above weight parts; Step 2: Evenly mix chromium oxide green and erbium oxide with a particle size of less than 0.074 mm, place them in a sagger and put them into a kiln, keep them warm and sinter them at a temperature of 1450-1500° C. for 2-4 hours, and after taking them out of the kiln, ball mill them for 2-4 hours to obtain a mixture for standby use; Step 3: Put chrome corundum particles with a particle size of 4-1mm, aluminum chrome slag particles with a particle size of 1-0mm, and fused brown corundum particles with a particle size of 3-1mm into a sand mixer according to the above proportions, add phosphoric acid and mix and grind for 1-2 minutes; Step 4: Place fused white corundum powder with a particle size of less than 0.074 mm, alumina powder with a particle size of less than 6 μm, and 6.5-9.5 parts by weight of the mixture prepared in step 2 in a premixer and mix for 1-2 minutes to obtain a premixed fine powder; Step 5: Add the premixed fine powder obtained in step 4 to the mixing and grinding equipment in step 3, wet-grind for 5-7 minutes, trap the material for 22-26 hours, and after forming, dry it at 200°C for 24 hours to obtain the Al2O3-Cr2O3 refractory material resistant to H2 and CO erosion for hydrogen-based vertical furnaces.
[0009] In the preparation process of the present invention, chromium oxide green and erbium oxide are first pre-fired. After the pre-reaction of chromium oxide green and erbium oxide, CrErO3 composite crystal phase is obtained after high-temperature firing. In the later use under high-temperature environment, chromium oxide particles and aluminum oxide micropowder form (Cr, Al)2O3 solid solution. This solid solution not only promotes inter-particle bonding, but also can form (Cr, Al, Er)2O3 composite solid solution with CrErO3. This composite solid solution has a significant effect on resisting H2 and CO gas corrosion. At the same time, under the action of SiO2 in the composite solid solution system, Cr2O3 is loaded on Er2O3, which further improves the surface structure of Er2O3. Chromium oxide and SiO2 entering the system work together to increase the specific surface area of the product, stabilize the metastable Er2O3, and improve the thermal stability of the finished product; and the slag corrosion resistance and thermal shock stability are significantly improved.
[0010] In addition, the monoclinic structure of erbium oxide transforms into a hexagonal crystal phase after firing, and expands at the same time, generating a certain amount of microcracks in the aluminum-chrome brick body. These microcracks provide space for expansion, relieve thermal stress, and thus improve thermal shock resistance and overall increase the service life of the refractory material. The addition of erbium oxide in the form of micropowder effectively promotes sintering, and combines well with other refractory materials at low temperatures, so that some through pores are closed, further improving the density and strength of the product; the erbium oxide micropowder penetrates into the whiskers of the (Cr, Al, Er)2O3 composite solid solution in the subsequent reaction, playing a secondary protective role.
[0011] Steps 3 and 4 are used to mix the coarse material and the fine material respectively. Premixing the matrices of different particle sizes in advance can make the raw materials fully mixed and uniform, avoid errors and unevenness caused by direct mixing, and shorten the time for subsequent mixing of the coarse material and the fine material. Finally, the premixed fine powder is added to the premixed coarse powder, and wet milling is performed to obtain the final refractory material.
[0012] Among them, chrome corundum has good high-temperature thermal stability and erosion resistance, which ensures the high-temperature resistance, good oxidation resistance and corrosion resistance of the refractory material, as well as good thermal shock resistance.
[0013] Among them, aluminum chromium slag, a part of waste aluminum chromium slag is used to reduce chromium pollution and reduce the cost of refractory materials. The raw material itself has high hardness and density.
[0014] Among them, fused brown corundum has a low thermal expansion coefficient and good corrosion resistance, making the refractory material more resistant to erosion.
[0015] Among them, the thermal expansion coefficient of fused white corundum is small, which can make the thermal expansion of the refractory material smaller and make the refractory material more stable. Beneficial Effects
[0016] (1) The present invention selects brown corundum with higher density and utilizes the impurities in the brown corundum material to provide a certain liquid phase during the firing process, which helps to promote liquid phase sintering and improve the density of the material.
[0017] (2) The present invention utilizes aluminum-chrome slag obtained by crushing waste aluminum-chrome bricks, thereby solving the problem of waste chromium pollution and reducing the cost of aluminum-chrome bricks.
[0018] (3) The present invention forms a (Cr, Al, Er)2O3 composite solid solution in a high temperature environment in the later stage of use; this composite solid solution has a significant effect on resisting H2 and CO erosion; the monoclinic structure of erbium oxide is transformed into a hexagonal crystal phase after firing, and expansion occurs at the same time, generating a certain amount of microcracks in the aluminum-chrome brick body, these microcracks provide space required for expansion, relieve thermal stress, thereby improving thermal shock resistance, and overall improving the service life of the refractory material; the compressive strength after H2 erosion for 24 hours can reach 130-140MPa, and the compressive strength after CO erosion for 24 hours can reach 130-150MPa.
[0019] (4) The Al2O3-Cr2O3 refractory material for hydrogen-based vertical furnaces resistant to H2 and CO erosion in the present invention has good resistance to H2 and CO gas erosion, slag erosion and stable high-temperature performance, which improves the overall life of the hydrogen-based vertical furnace. The refractory material in the present invention has obvious economic benefits, forms a technical advantage for manufacturers, has a higher premium, and has a longer service life for users, diluting the use cost. DETAILED DESCRIPTION
[0020] The weight percentage of Cr2O3 in the chrome corundum particles used in the following examples is ≥96%; the weight percentage of Cr2O3 in the aluminum chrome slag particles is ≥36%; the weight percentage of Al2O3 in the fused white corundum powder is ≥99.5%; the weight percentage of Al2O3 in the fused brown corundum particles is ≥95%; the weight percentage of Al2O3 in the alumina powder is ≥99.5%; the weight percentage of H3PO4 in phosphoric acid is ≥85%
[0021] Implementation 1: The Al2O3-Cr2O3 refractory material for hydrogen-based vertical furnace resistant to H2 and CO corrosion of this embodiment is prepared according to the following steps: Step 1, weighing each raw material according to the above weight parts; Step 2: Evenly mix 5 parts of chromium oxide green with a particle size less than 0.074 mm and 3 parts of erbium oxide, place them in a sagger, put them into a kiln and heat them for 2 hours at a temperature of 1450° C., and then ball-mill them for 2 hours before use; Step 3: Put 40 parts of chrome corundum particles with a particle size of 4-1mm, 10 parts of aluminum chrome slag particles with a particle size of 1-0mm, and 10 parts of fused brown corundum particles with a particle size of 3-1mm into a sand mixer, add 3 parts of phosphoric acid, and mix and grind for 1 minute; Step 4: 30 parts of fused white corundum powder with a particle size of less than 0.074 mm, 5 parts of alumina powder with a particle size of less than 6 μm, and 6.5 parts of the powder obtained in step 2 are placed in a premixer and mixed for 1 minute to obtain a premixed fine powder; Step 5: Add the premixed fine powder obtained in step 4 to the mixing and grinding equipment in step 3, wet-grind for 7 minutes, trap the material for 22 hours, and dry at 200°C for 24 hours after forming to obtain the Al2O3-Cr2O3 refractory material resistant to H2 and CO corrosion for hydrogen-based vertical furnaces.
[0022] Embodiment 2: The Al2O3-Cr2O3 refractory material for hydrogen-based vertical furnace resistant to H2 and CO corrosion of this embodiment is prepared according to the following steps: Step 1, weighing each raw material according to the above weight parts; Step 2: Evenly mix 3 parts of chromium oxide green with a particle size less than 0.074 mm and 10 parts of erbium oxide, place them in a sagger, put them into a kiln and heat them for 4 hours at a temperature of 1500° C., and then ball-mill them for 4 hours before use; Step 3: Put 30 parts of chrome corundum particles with a particle size of 4-1mm, 15 parts of aluminum chrome slag particles with a particle size of 1-0mm, and 20 parts of fused brown corundum particles with a particle size of 3-1mm into a sand mixer, add 4 parts of phosphoric acid and mix for 2 minutes; Step 4: 20 parts of fused white corundum powder with a particle size of less than 0.074 mm, 10 parts of alumina powder with a particle size of less than 6 μm, and 9.5 parts of the powder obtained in step 2 are placed in a premixer and mixed for 2 minutes to obtain a premixed fine powder; Step 5: Add the premixed fine powder obtained in step 4 to the mixing and grinding equipment in step 3, wet-grind for 5 minutes, trap the material for 26 hours, and dry at 200°C for 24 hours after molding to obtain the Al2O3-Cr2O3 refractory material resistant to H2 and CO corrosion for hydrogen-based vertical furnaces.
[0023] Comparative Example 1 (the following parts are by weight) Step 1: Put 30 parts of chrome corundum particles with a particle size of 4-1mm, 15 parts of aluminum chrome slag particles with a particle size of 1-0mm, and 15 parts of fused brown corundum particles with a particle size of 3-1mm into a sand mixer, add 4 parts of phosphoric acid and mix for 2 minutes; Step 2: 30 parts of fused white corundum powder with a particle size of less than 0.074 mm, 5 parts of alumina powder with a particle size of less than 6 μm, and 3 parts of chrome green are placed in a premixer and mixed for 3 minutes to obtain a premixed fine powder; Step 3: Add the premixed fine powder obtained in step 1 to the mixing and grinding equipment in step 3, wet-grind for 4 minutes, trap the material for 24 hours, and then form it and dry it at 200°C for 24 hours to obtain the corrosion-resistant alumina-chromium oxide refractory material.
[0024] Comparative Example 2 (the following parts are by weight) Step 1: put 25 parts of chrome corundum particles with a particle size of 4-1mm, 10 parts of aluminum chrome slag particles with a particle size of 1-0mm, and 20 parts of fused brown corundum particles with a particle size of 3-1mm into a sand mixer, add 4 parts of phosphoric acid and mix for 3 minutes; Step 2: Place 35 parts of fused white corundum powder with a particle size of less than 0.074 mm, 8 parts of alumina powder with a particle size of less than 6 μm, and 4 parts of chromium oxide green in a premixer and mix for 1 minute to obtain a premixed fine powder; Step 3: Add the premixed fine powder obtained in step 1 to the mixing and grinding equipment in step 3, wet-grind for 8 minutes, trap the material for 24 hours, and then form it and dry it at 200°C for 24 hours to obtain the corrosion-resistant alumina-chromium oxide refractory material.
[0025] The laboratory test indicators of the refractory materials obtained in Example 1-2 and Comparative Example 1-2 are shown in Table 1. Among them, the standards used for the test are: the preparation method of refractory product samples adopts GB / T7321, the bulk density and true porosity test methods adopt GB / T2997, the chemical analysis adopts GB / T6900, the room temperature compressive strength adopts GB / T5072.1, the heating permanent line change adopts GB / T5988, and the load softening temperature adopts YB / T370.
[0026] Table 1 Performance indicators of refractory materials prepared in Examples 1-2 and Comparative Examples 1-2
[0027] As shown in Table 1, compared with Comparative Examples 1-2, the refractory material prepared in Example 1-2 has better performance, which is mainly because its room temperature compressive strength is higher, the linear change rate is smaller under high temperature conditions, the high temperature load softening temperature is higher and the thermal shock resistance is better, which can ensure the initial use of the refractory material under the special working conditions of the hydrogen-based vertical furnace. At the same time, as time goes by, its compressive strength decays less under H2 and CO erosion, and its anti-erosion effect is the best. The process ratio of the present invention shows good resistance to H2 and CO erosion, which can increase the service life of the furnace in the complex working environment of the hydrogen-based vertical furnace and create good economic benefits.
Claims
1. A hydrogen-based vertical furnace resistant to H2 and CO erosion alumina-chromium oxide refractory, characterized in that: The invention comprises the following raw materials in parts by weight: 30-40 parts of chrome corundum particles with a particle size of 4-1 mm; 10-15 parts of aluminum chrome slag particles with a particle size of 1-0 mm; 10-20 parts of fused brown corundum particles with a particle size of 3-1 mm; 20-30 parts of fused white corundum powder with a particle size less than 0.074 mm; 5-10 parts of aluminum oxide powder with a particle size less than 6 μm; 3-5 parts of chromium oxide green with a particle size less than 0.074 mm; 3-4 parts of phosphoric acid; and 3-10 parts of erbium oxide.
2. The alumina-chromium oxide refractory material for hydrogen-based vertical furnaces resistant to H2 and CO corrosion according to claim 1, characterized in that: The weight proportion of Cr2O3 in chrome corundum particles is ≥96%, the weight proportion of Al2O3 in fused white corundum powder is ≥99.5%, and the weight proportion of Al2O3 in alumina micropowder is ≥99.5%.
3. The alumina-chromium oxide refractory material for hydrogen-based vertical furnaces resistant to H2 and CO corrosion according to claim 1, characterized in that: The aluminum-chrome slag is obtained by crushing waste aluminum-chrome bricks, and the weight proportion of Cr2O3 in the aluminum-chrome slag particles is ≥36%.
4. The alumina-chromium oxide refractory material for hydrogen-based vertical furnaces resistant to H2 and CO corrosion according to claim 1, characterized in that: H3PO4 in phosphoric acid ≥ 85%.
5. The alumina-chromium oxide refractory material for hydrogen-based vertical furnaces resistant to H2 and CO corrosion according to claim 1, characterized in that: The particle size of erbium oxide is 5um.
6. The method for preparing a H2 and CO resistant alumina-chromium oxide refractory for a hydrogen-based vertical furnace according to claim 1, characterized in that: Step 1, weigh each raw material according to the above weight parts; Step 2: Evenly mix chromium oxide green and erbium oxide with a particle size of less than 0.074 mm, place them in a sagger and put them into a kiln, keep them warm and sinter them at a temperature of 1450-1500° C. for 2-4 hours, and after taking them out of the kiln, ball mill them for 2-4 hours to obtain a mixture for standby use; Step 3: Put chrome corundum particles with a particle size of 4-1mm, aluminum chrome slag particles with a particle size of 1-0mm, and fused brown corundum particles with a particle size of 3-1mm into a sand mixer according to the above proportions, add phosphoric acid and mix and grind for 1-2 minutes; Step 4: Place fused white corundum powder with a particle size of less than 0.074 mm, alumina powder with a particle size of less than 6 μm, and 6.5-9.5 parts by weight of the mixture prepared in step 2 in a premixer and mix for 1-2 minutes to obtain a premixed fine powder; Step 5: Add the premixed fine powder obtained in step 4 to the mixing and grinding equipment in step 3, wet-grind for 5-7 minutes, trap the material for 22-26 hours, and after forming, dry it at 200°C for 24 hours to obtain the Al2O3-Cr2O3 refractory material resistant to H2 and CO erosion for hydrogen-based vertical furnaces.
Citation Information
Cited By
Furnace lining structure and preparation method thereof
CN121994027A